Factors Contributing to The Success of Strategic Alliance in Penetrating New Markets: A Study of Multinational Corporations in Malaysia - Khor, Siu Gek (2010)
The main purpose of this research is to ascertain the factors contributing to alliance success and examine the relationship between the variables.